(untitled) (The Peerian Journal, 2025)
With the development of the digital world and the internet, word-of-mouth marketing has found a new platform for activity. Social media marketing has transformed the concept of word-of-mouth marketing. One of the most important outcomes of social media is the emergence of online wordof-mouth marketing among members of these networks, which is one of its most important applications. Tourism has always been a phenomenon of great importance, and based on expectations, it will become the most profitable industry in the world, including urban tourism. Therefore, this research aims to examine the factors influencing online word-of-mouth marketing in the growth of the urban tourism economy (case study: Karbala). The research is a descriptive survey. The statistical sample included, as a first stage, 13 workers after obtaining the experts’ approval as a first stage for interviews, and 56 tourists from Karbala, who were selected and interviewed non-randomly. Data and scenarios were analyzed using fuzzy cognitive mapping techniques, and a research model was designed using social network analysis. These factors were considered the most important by tourists, given their centrality. Finally, based on the results, proposals were presented for developing online word-of-mouth marketing to grow the urban tourism economy (case study: Karbala).